Catalytic Pyrolysis of Coconut Copra and Rice Husk for Possible Maximum Production of Bio-Oil - Balansundram, Vekes; Norazana, Ibrahim; Rafiziana, M. Kasman; Mohd Kamarudin, Abd Hamid; Ruzinah, Isha; Hasrinah, Hasbullah; Roshafima, Rasit Ali (AIDIC Servizi, 2017)
The main objective of the present work is to study the effect of the nickel catalyst on pyrolysis of coconut copra and rice husk via thermo gravimetric analysis (TGA). The optimisation of catalyst weight ratio on biomass is also determined. The sample is pyrolysed from 30 °C up to 700 °C at 10 °C/min of heating rate in nitrogen (N2) environment flowing at 150 mL/min. The catalyst (Ni-Ce/Al2O3) was prepared via wet impregnation method, with alumina (Al2O3) as support, while cerium (Ce) and nickel (Ni) act as promoter. The samples were prepared accordingly with biomass to catalyst weight loading ratio and labelled as follows; rice husk as RH-2 (1 : 0.15)and RH-3 (1 : 0.50) including coconut copra as CC-2 (1 : 0.15) and CC-3 (1 : 0.50). For comparison, the pyrolysis of coconut copra and rice husk without catalyst also are conducted at the same operating condition and named as CC-1 (1 : 0) and RH-1 (1 : 0). The TGA-DTG curves show that, the presences of catalyst significantly affect the devolatilisation rate of biomass. The highest volatile matter was achieved by CC-2 at 83.27 % compared to RH-2 at only 46.66 %. Although at similar biomass to catalyst weight ratio of 1 : 0.15, the coconut copra is more favourable to yield a high volatile matter than the rice husk. At the same time, both biomass samples specifically CC-3 and RH-3 have achieved the highest in solid residual yield. Overall, the mass loss of volatile matter decreases in the order of CC-2 > CC-1 > CC-3 > RH-1 > RH-2 > RH-3. In summary, the optimum catalyst loading was at CC-2 and RH-2 that work best to degrade at the highest mass loss of volatile, in which attributes to higher yield of pyrolysis oil.